Work Inequalities in the Crisis : evidence from Europe - Vaughan-Whitehead, Daniel; International Labour Office (Cheltenham Edward Elgar Publishing Ltd., 2011)
This book offers a unique combination of research, case studies and policy discussions. An assessment of national trends in 30 European countries precedes case studies of 14 of them, in which noted European specialists report on individual enterprises or sectors. The volume’s survey of national- and local-level policy solutions contributes to identifying those responses that strengthen economic competitiveness, preserve social cohesion and do not deepen inequalities. This timely resource will be of particular interest to academics, students and researchers in labour economics, to policymakers, and to those involved in European studies more generally.
​1. Introduction: Has the Crisis Exacerbated Work Inequalities? / Daniel Vaughan-Whitehead -- 2. Mixed Adjustment Forms and Inequality Effects in Estonia, Latvia and Lithuania / Jaan Masso and Kerly Krillo -- 3. Inequality at Work Emerging in the Current Crisis in Bulgaria / Vasil Tzanov -- 4. Croatia: Prolonged Crisis with an Uncertain Ending / Vojmir Franičević -- 5. France: Protecting the Insiders in the Crisis and Forgetting the Outsiders? / Jérôme Gautié -- 6. The German Labour Market after the Financial Crisis: Miracle or Just a Good Policy Mix? / erhard Bosch -- 7. Hungary: Crisis Coupled with a Fiscal Squeeze – Effects on Inequality / János Köllő -- 8. Italy: Limited Policy Responses and Industrial Relations in flux, Leading to Aggravated equalities / Niall O’Higgins -- 9. The Netherlands: Is the Impact of the Financial Crisis on Inequalities Different from in the Past? / Wiemer Salverda -- 10. From the Highest Employment Growth to the Deepest Fall: Economic Crisis and Labour Inequalities in Spain / Rafael Muñoz de Bustillo Llorente and José-Ignacio Antón Pérez -- 11. Negotiated Flexibility in Sweden: A More Egalitarian Response to the Crisis? -- Dominique Anxo -- 12. Crisis in Turkey: Aggravating a Segmented Labour Market and Creating New Inequalities / Seyhan Erdoğdu -- 13. Social Impact of the Crisis in the United Kingdom: Focus on Gender and Age Inequalities / Damian Grimshaw and Anthony Rafferty -- Index
Published by Edward Elgar Pub. in association with International Labour Office
Includes bibliographical references and index.&nbsp
Keywords: Labour market; MANPOWER; EMPLOYMENT DISCRIMINATION; MONETARY CRISIS; EUROPE; CASE STUDIES